Conversion of the stacking orientation of bilayer graphene through high-pressure treatment. (February 2021) - Chen, Zhiying; Sui, Yanping; Li, Jing; Kang, He; Wang, Shuang; Zhao, Sunwen; Gao, Xiuli; Peng, Songang; Jin, Zhi; Liu, Xinyu; Zhang, Yanhui; Yu, Guanghui
Abstract: AB-stacked bilayer graphene (BLG) has wide application prospects in the field of optoelectronic devices. Chemical vapor deposition (CVD) is an important method used to prepare BLG, but no definite stacking orientation is observed between the bilayers. Besides AB stacking, a number of disordered stacking orientations that could seriously affect the performance of BLG also exist. In this paper, we report a method to control the stacking orientation of reverse-transferred CVD-BLG via high pressure environment. We found that the orientation of BLG could be changed from weak-coupling stacking to AB stacking by increasing the temperature of the solvent in the autoclave. MoS2 grains grown on graphene confirmed the stacking orientation variation of BLG. Reductions in the distance between layers in BLG under a high-pressure environment were considered to explain the observed orientation change. Reverse transfer allows the easy modification of the stacking orientation of BLG. The proposed high-pressure assistant method introduces a new route to prepare AB-stacked BLG and could be used to adjust the stacking direction of other two-dimensional materials. Graphical abstract: Increasing the pressure can change the distance between the two graphene layers, the distance reduced from d1 to d2 and the original stacking balance is modified. The stacking orientations of BLG can be determined by analyzing the orientation of MoS2 crystals grown in SLG and BLG regions. After high pressure treatment, the orientation of MoS2 crystals on the monolayer and bilayer is consistent. Image 1